2017
DOI: 10.1136/bmjopen-2016-013563
|View full text |Cite
|
Sign up to set email alerts
|

Emergency nurse disaster preparedness during mass gatherings: a cross-sectional survey of emergency nurses' perceptions in hospitals in Mecca, Saudi Arabia

Abstract: ObjectivesTo assess hospital emergency nurses' self-reported knowledge, role awareness and skills in disaster response with respect to the Hajj mass gathering in Mecca.DesignCross-sectional online survey with primary data collection and non-probabilistic purposive sample conducted in late 2014.SettingAll 4 public hospitals in Mecca, Saudi Arabia.Participants106 registered nurses in hospital emergency departments.Main outcome measureAwareness, knowledge, skills and perceptions of emergency nurses in Mecca with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
67
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(88 citation statements)
references
References 18 publications
2
67
1
5
Order By: Relevance
“…However, they were not trained for the same. 11 A study by Gundran et al, 29 also conducted a similar study including 91 participants. Most of the participants, 98.4% in the present study and 97.8% in the study by Gundran et al, 29 considered training necessary for all healthcare workers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they were not trained for the same. 11 A study by Gundran et al, 29 also conducted a similar study including 91 participants. Most of the participants, 98.4% in the present study and 97.8% in the study by Gundran et al, 29 considered training necessary for all healthcare workers.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study assessing the knowledge and skills among emergency nurses showed that they were confident in terms of disaster handling, but they were not trained for the same. 11 Another study was performed on nurses reported average percentage scores in the domains of knowledge, attitudes and practice towords disaster and emergency preparedness. 12 A growing number of studies in the literature reported facts about Kingdom of Saudi Arabia's disaster management and preparedness.…”
mentioning
confidence: 99%
“…Di antara 10 jurnal yang direview, terdapat 5 jurnal yang memiliki desain cross sectional (Alzahrani & Kyratsis, 2017), (Berhanu, Abrha, Ejigu, & Woldemichael, 2016), (Labrague et al, 2016), (Tzeng et al, 2016), dan (Seyedin et al, 2015) , 4 jurnal yang menggunakan penelitian kualitatif (Rabiei, Nakhaee, & Pourhosseini, 2014), (Yu et al, 2013), (Moghaddam, Saeed, Khanjani, & Arab, 2014) dan (Shabanikiya, Gorgi, Seyedin, & Jafari, 2016) dan 1 jurnal yang menggunakan Studi deskriptif (Yan et al, 2015). Dari 10 jurnal yang direview, terdapat 9 jurnal menggunakan program pendidikan dan pelatihan manajemen bencana (Alzahrani & Kyratsis, 2017); (Berhanu et al, 2016); (Rabiei et al, 2014); (Yu et al, 2013); (Moghaddam et al, 2014); (Labrague et al, 2016); (Tzeng et al, 2016); (Yan et al, 2015); dan (Seyedin et al, 2015) Pernyataan peneliti dari penelitian tersebut didukung oleh teori Happell (2009) yang menyatakan bahwa perawat berada dalam posisi untuk membantu mengatasi kesehatan jiwa pada saat krisis atau bencana, maka diperlukan dukungan psikologis berupa pengetahuan, yang mana pengetahuan tersebut terkait dengan teknik intervensi krisis dan bencana yang merupakan suatu keterampilan klinis yang penting bagi semua perawat, di luar dari tatanan klinis atau praktik spesialis (Happell et al, 2009dalam Stuart, 2016. Disamping itu, pelatihan manajemen penanggulangan bencana sangat jarang dilakukan kepada tenaga perawat di pelayanan maupun di pendidikan, sehingga keterampilan, pengetahuan dan keahlian perawat dalam penanggulangan bencana tidak sesuai prosedur dan membuat penangganan bencana berjalan lambat dan tidak efektif ((Tzeng et al, 2016); (Yan et al, 2015); dan (Yu et al, 2013)).…”
Section: Metodeunclassified
“…Pada bagian selatan dan timur Indonesia terdapat sabuk vulkanik (volcanic arc) yang memanjang dari pulau Sumatera-Jawa-Nusa-Tenggara-Sulawesi, yang sisinya berupa pegunungan vulkanik dan dataran rendah yang sebagian besar didominasi oleh rawarawa. Kondisi tersebut sangat berpotensi sekaligus terjadinya rawan bencana seperti letusan gunung berapi, gempa bumi, tsunami, banjir dan tanah longsor (Alzahrani & Kyratsis, 2017).…”
unclassified
See 1 more Smart Citation